1992
DOI: 10.1117/12.137883
|View full text |Cite
|
Sign up to set email alerts
|

<title>NOVAM evaluation from aerosol and lidar measurements in a tropical marine environment</title>

Abstract: NOVAM, the Naval Oceanic Vertical Aerosol Model, has been developed to predict the non-unifoni and nonlogarithinic extinction profiles that are often observed in the iarine atiospheric boundary layer. The kernel of NOVAN is the Navy Aerosol Model (NAN) that calculates the aerosol size distribution at 10 ii ASL froi meteorological paralueters. The aerosol profile is calculated from the surface layer size distribution with a physical model. Extinction profiles are calculated froi the aerosol profiles using a Mie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The same applies to the water temperature. A recent analysis of aerosol measurements at locations with different water temperatures (10-30øC) has indicated that this effect may indeed be important [de Leeuw and Kunz, 1992]. The role of relative humidity must also be considered because particles grow and shrink in response to variations in this parameter.…”
mentioning
confidence: 99%
“…The same applies to the water temperature. A recent analysis of aerosol measurements at locations with different water temperatures (10-30øC) has indicated that this effect may indeed be important [de Leeuw and Kunz, 1992]. The role of relative humidity must also be considered because particles grow and shrink in response to variations in this parameter.…”
mentioning
confidence: 99%
“…[7,8,9,10]. In this experiment, the surface observations were made with an instrumented fishing boat.…”
Section: Testing the Novam Conceptsmentioning
confidence: 99%